2021
DOI: 10.1038/s41598-021-03407-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proportionate cardiovascular mortality in patients with chronic infectious and inflammatory conditions in the United States, 1999–2018

Abstract: Treatment options for several chronic infectious and inflammatory conditions have expanded in recent years. This may have implications for evolving competing risks for chronic inflammation-associated comorbidities, including cardiovascular diseases (CVDs). Yet sparse data exist on patterns over time in cardiovascular mortality for chronic infectious and inflammatory conditions. We used data from the Centers for Disease Control and Prevention 1999–2018 Multiple Causes of Death database to investigate patterns i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…However, lipid profile monitoring in IBD patients is not routinely performed in Taiwan. Additionally, awareness of hyperlipidemia is lower than that of diabetes and hypertension; therefore, hyperlipidemia is diagnosed only when physical complications, such as CVD accompanied by chest pain ( 58 ). Thus, hyperlipidemia is rarely managed in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…However, lipid profile monitoring in IBD patients is not routinely performed in Taiwan. Additionally, awareness of hyperlipidemia is lower than that of diabetes and hypertension; therefore, hyperlipidemia is diagnosed only when physical complications, such as CVD accompanied by chest pain ( 58 ). Thus, hyperlipidemia is rarely managed in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Code lists were supplemented after review of 27 code lists from existing published literature [31][32][33][34][35][36][37][38][39][40][41][42][43][44], with the final list of individual codes detailed in Appendix 1 Tables S24 to S44.…”
Section: Outcome Events and Safety Searchmentioning
confidence: 99%
“…Epidemiological studies have increasingly linked certain chronic viral infections with elevated risk of CVD, such as HSV, hepatitis C virus (HCV), CMV, HPV, and HIV. However, there is a significant controversy due to conflicting results from previous studies, with some reporting inverse or null association between chronic viral infection and cardiovascular outcomes 10–19 . In a cohort study involving 4809 chronic hepatitis C patients and 71 668 matched controls, no increased myocardial infarction risk was found among the infected compared to the uninfected over a median follow‐up period of 3.2 years 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a significant controversy due to conflicting results from previous studies, with some reporting inverse or null association between chronic viral infection and cardiovascular outcomes. [10][11][12][13][14][15][16][17][18][19] In a cohort study involving 4809 chronic hepatitis C patients and 71 668 matched controls, no increased myocardial infarction risk was found among the infected compared to the uninfected over a median follow-up period of 3.2 years. 13 A 2022 study utilizing UK Biobank (UKB) data with 9429 participants found that seropositivity to common herpes virus was not associated with higher risk of stroke, myocardial infarction, or all-cause mortality.…”
mentioning
confidence: 97%